Association of G20210A Prothrombin Gene Mutation and Cerebral Ischemic Stroke in Young Patients - Poudel, Sujan (Cureus, 2020)
Ischemic stroke is an acute episode of neurological dysfunction resulting from the focal brain and spinal cord infarction. Many etiologies have been reported and vary significantly with the age of the patients. This study aims to show the association of G20210A prothrombin gene mutation and cerebral ischemic stroke in young patients. The prothrombin gene mutation is the second most common inherited thrombophilia after the factor V mutation. In this single missense mutation, guanine is substituted by adenine base pair in the nucleotide position 20210 of the 3'-untranslated region of the prothrombin gene, resulting in abnormal thrombin production predisposing to both arterial or venous thrombosis. Forty-seven relevant articles were selected after a thorough screening process using a regular keyword ‘G20210A Prothrombin’ and/or ‘Ischemic Stroke’ mostly from the PubMed database. We included the studies that are published in the last 22 years with patients age ≤57 years. This review article depicts the association of G20210A prothrombin gene mutation with ischemic stroke in young patients irrespective of ethnicity and zygosity status of their genotype. However, more multicenter prospective studies are needed to better understand the application of prothrombin gene mutation in predicting the associated risk of ischemic stroke in young patients and its importance in deciding the patients' treatment or prognosis.